Epizootic Situation in the Mongolian Part of the Transboundary Sailugem Natural Plague Focus in 2018 - V. M. Korzun; S. V. Balakhonov; A. V. Denisov; E. N. Rozhdestvensky; E. G. Tokmakova; P. P. Sanarov; S. S. Akulova; S. A. Kosilko; D. Otgonbayar; L. Orgilbayar; D. Batzhav; Ch. Urzhikh; et al. (Проблемы особо опасных инфекций, 2019)
Objective of the study was monitoring of epizootic situation in the Mongolian part of the trans-boundary Sailugem natural plague focus through 2018 for optimization of preventive and anti-epidemic activities to decrease the level of risk of human plague cases among the population in the border areas of Mongolia and Russia.Materials and methods. Epizootic survey was conducted across the area of 2668 km2 ; 282 mammals, 261 ectoparasites, including 257 fleas, were tested for plague. All laboratory investigations of the field material were carried out in the mobile laboratory for monitoring and diagnostics, mounted on the platform of KAMAZ. Field samples were subjected to molecular-genetic (PCR) and serological tests. Fresh and mummified pickings of birds of prey, corpses, caught rodents and lagomorphs, fleas collected from corpses, were tested using immune-chromatographic method (ICM) to detect capsular antigen (F1) of plague microbe. PCR and ICM positive samples were investigated applying bacteriological method. In the course of epizootiological survey, GIS-tools were employed. All the results obtained were plotted on electronic maps using QGIS 2.12.3 software package.Results and discussion. The total of 47 Yersinia pestis ssp. pestis strains were isolated from grey marmots and their fleas. Y. pestis DNA was detected in 60 objects. Serological testing showed 60 positive results. Contamination of the caught souslik with plague agent reached 4.5 % (n=22), fresh corpses and picking of predatory birds – 63.4 % (n=41), mummified corpses and leftovers, skeletal remains – 10.0 % (n=140). It was established that in the border territory, adjacent to Russia, an intensive diffused plague epizooty, caused by the agent of the main subspecies, takes place. All epizootic manifestations were revealed at the altitudes of 2400–2800 m above sea level, in densely populated grey marmot settlements. The epizooty was registered in most of the southern macro-slope of Sailugem ridge, throughout 100 km and along the whole Karalakhtu ridge – throughout 30 km. The epizooty area, confirmed by plague agent isolation, amounted to 1207 km2 (45.2 % of the examined territory).